Cropland Carbon Uptake Delayed and Reduced by 2019 Midwest Floods. Issue 1 (25th March 2020) - Yin, Yi; Byrne, Brendan; Liu, Junjie; Wennberg, Paul O.; Davis, Kenneth J.; Magney, Troy; Köhler, Philipp; He, Liyin; Jeyaram, Rupesh; Humphrey, Vincent; Gerken, Tobias; Feng, Sha; et al.
Abstract: While large‐scale floods directly impact human lives and infrastructures, they also profoundly impact agricultural productivity. New satellite observations of vegetation activity and atmospheric CO2 offer the opportunity to quantify the effects of such extreme events on cropland carbon sequestration. Widespread flooding during spring and early summer 2019 induced conditions that delayed crop planting across the U.S. Midwest. As a result, satellite observations of solar‐induced chlorophyll fluorescence from TROPOspheric Monitoring Instrument and Orbiting Carbon Observatory reveal a 16‐day shift in the seasonal cycle of photosynthesis relative to 2018, along with a 15% lower peak value. We estimate a reduction of 0.21 PgC in cropland gross primary productivity in June and July, partially compensated in August and September (+0.14 PgC). The extension of the 2019 growing season into late September is likely to have benefited from increased water availability and late‐season temperature. Ultimately, this change is predicted to reduce the crop productivity in the Midwest Corn/Soy belt by 15% compared to 2018. Using an atmospheric transport model, we show that a decline of 0.1 PgC in the net carbon uptake during June and July is consistent with observed CO2 enhancements of up to 10 ppm in the midday boundary layer from Atmospheric Carbon and Transport‐America aircraft and over 3 ppm in column‐averaged dry‐air mole fractions from Orbiting Carbon Observatory. This study quantifies the impact of floods on cropland productivity and demonstrates the potential of combining solar‐induced chlorophyll fluorescence with atmospheric CO2 observations to monitor regional carbon flux anomalies. Plain Language Summary: Widespread flooding and inundation across the U.S. Midwest during spring and early summer 2019 forced many farmers to delay crop planting. New satellite observations of vegetation photosynthesis and atmospheric CO2 offer the opportunity to quantify the effects of such events on cropland carbon sequestration. We show that the delayed planting resulted in a shift of 16 days in the seasonal cycle of the crop growth and a 15% lower peak solar‐induced chlorophyll fluorescence value. We estimate a reduction of 0.21 PgC in the gross primary production during June and July, partially compensated in August and September (+0.14 PgC). The extension of the 2019 growing season into late September is likely to have benefited from increased water availability and late‐season temperature. Ultimately, this change is predicted to reduce the crop production over most of the Midwest Corn/Soy belt by 15%, based on the strong empirical correlation between 2018 growing season SIF and crop yield. The bottom‐up estimated net carbon uptake reduction of 0.1 PgC in June and July is consistently supported by top‐down inferred CO2 anomalies from both aircraft and satellite observations. We anticipate that such a rapid event detection can benefit agricultural and natural resource management and ecological forecasting efforts. Key Points: Flood‐induced delay in crop planting shifted the 2019 SIF seasonal cycle by 16 days and reduced the peak value by 15% compared to 2018 A 0.1 PgC reduction in Midwest net ecosystem uptake during June and July is consistent with the observed increase in atmospheric CO2 The 2019 flood induced a 0.06 PgC reduction in the annual GPP of croplands (−4%) but a 0.04 PgC increase for natural vegetation (+3%)